CERVICAL MUCUS FERN PATTERN IN RELATION TO FERTILITY AND MICRO-MINERAL PROFILE IN ANESTRUS SURTI BUFFALOES SUBJECTED TO OVSYNCH ALONE AND IN COMBINATION WITH PRID - SAVANI, H R; KHASATIYA, C T; SAXENA, S; PATEL, M D; PATEL, V R; MODI, L C; CHAUDHARI, N C (The Indian Journal of Animal Reproduction, 2022)
Eighteen anestrus Surti buffaloes were subjected to Ovsynch or Ovsynch plus PRID or inseminated at spontaneous estrus (n=6 in each group). Overall conception rate was 77.8% in buffaloes with typical fern pattern as compared to 42.8% with atypical fern pattern. Serum copper, zinc, iron and manganese concentrations were similar (p>0.05) between animals during the study period.